In finger osteoarthritis, change in synovitis is associated with change in pain on a joint-level; a longitudinal magnetic resonance imaging study. Issue 7 (July 2019) - van Beest, S.; Damman, W.; Liu, R.; Reijnierse, M.; Rosendaal, F.R.; Kloppenburg, M.
Summary: Objective: To investigate determinants of decrease and increase in joint pain in symptomatic finger osteoarthritis (OA) on magnetic resonance (MR) imaging over 2 years. Design: Eighty-five patients (81.2% women, mean age 59.2 years) with primary hand OA (89.4% fulfilling American College of Rheumatology (ACR) classification criteria) from a rheumatology outpatient clinic received contrast-enhanced MR imaging (1.5T) and physical examination of the right interphalangeal finger joints 2–5 at baseline and at follow-up 2 years later. MR images were scored paired in unknown time order, following the Hand OA MRI scoring system (HOAMRIS). Joint pain upon palpation was assessed by research nurses. Odds ratios (ORs; 95% confidence intervals) were estimated on joint level ( n = 680), using generalized estimating equations (GEE) to account for the within patient effects. Additional adjustments were made for change in MR-defined osteophytes, synovitis, and bone marrow lesions (BMLs). Results: Of 116 painful joints at baseline, at follow-up: 76 had less pain, 21 less synovitis, and 13 less BMLs. A decrease in synovitis (OR = 5.9; 1.12─31.0), but not in BMLs (OR = 0.39; 0.10─1.50), was associated with less pain. Of 678 joints without maximum baseline pain, at follow-up: 115 had increased pain, 132 increased synovitis, 96 increased BMLs, and 44 increased osteophytes. Increased synovitis (OR = 1.81; 1.11─2.94), osteophytes (OR = 2.75; 1.59─4.8), but not BMLs (OR = 1.14; 0.81─1.60), was associated with increased pain. Through stratification it became apparent that BMLs were mainly acting as effect modifier of the synovitis–pain association. Conclusion: Decrease in MR-defined synovitis is associated with reduced joint pain, identifying synovitis as a possible target for treatment of finger OA.